2021
DOI: 10.1038/s41598-021-81135-5
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic changes and educational inequalities in traffic fatalities in the Baltic countries and Finland in 2000–2015: a register-based study

Abstract: This study examined trends and inequalities in road traffic accident (RTA) mortality in the Baltic countries (Estonia, Latvia, Lithuania) and Finland in relation to large-scale macroeconomic changes in the 2000s. Educational inequalities in RTA mortality in 2000–2003, 2004–2007, 2008–2011 and 2012–2015 among 30–74 year olds were examined using census-linked longitudinal mortality data and by estimating the relative and slope index of inequality. Overall RTA mortality decreased substantially between 2000–2003 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…They concluded that the financial intervention did not bear an impact on road safety in these five countries. Stickley et al ( 2021 ) studied educational inequalities and macroeconomic changes during the 2000s in the Baltic countries (Estonia, Latvia, and Lithuania) and Finland. They observed that the number of deaths decreased more in the Baltic countries than in Finland.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that the financial intervention did not bear an impact on road safety in these five countries. Stickley et al ( 2021 ) studied educational inequalities and macroeconomic changes during the 2000s in the Baltic countries (Estonia, Latvia, and Lithuania) and Finland. They observed that the number of deaths decreased more in the Baltic countries than in Finland.…”
Section: Literature Reviewmentioning
confidence: 99%
“…European studies also reveal the presence of socioeconomic inequalities in road-traffic injury and the related mortality rates (Hasselberg et al, 2005;Stickley et al, 2021). 1 Especially in light of recent technological innovations concerting vehicles safety measures, access to safer vehicles represents a key source of the observed socio-economic gradient in road accident fatalities (Harper et al, 2015;Stickley et al, 2021) along with unsafe behaviours such as drunk-driving (Impinen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…European studies also reveal the presence of socioeconomic inequalities in road-traffic injury and the related mortality rates (Hasselberg et al, 2005;Stickley et al, 2021). 1 Especially in light of recent technological innovations concerting vehicles safety measures, access to safer vehicles represents a key source of the observed socio-economic gradient in road accident fatalities (Harper et al, 2015;Stickley et al, 2021) along with unsafe behaviours such as drunk-driving (Impinen et al, 2011). However, probably due to the limited availability of data on vehicle characteristics, matched with individual characteristics (Anbarci et al, 2009), including socio-economic status (SES), there is a lack of empirical evidence on socioeconomic inequalities in ownership of passively safer vehicles and their main underlying sources.…”
Section: Introductionmentioning
confidence: 99%